Unplanned Urban Expansion, Informality, and Land Stress in Secondary Cities - Paul (Sr.), Stanley Anthony Vivion; Joseph, Justin; Paul (Jr.), Stanley Anthony Vivion; Solomon, Orande Kenneatior (Stallion Journal for Multidisciplinary Associated Research Studies, 2026)
This article examines why secondary cities in developing countries are increasingly shaped by unplanned expansion, informal settlement growth, and mounting land stress. It argues that the problem is not urban growth itself, but the mismatch between demographic expansion and the institutional capacity to govern land, infrastructure, and service delivery. Where planning systems are rigid, registration costly, and serviced land scarce, urbanization proceeds informally through peripheral occupation, hazard exposure, and fragmented infrastructure. The article contends that secondary cities deserve far greater policy attention because they are often the fastest-growing urban nodes but the least institutionally prepared. Effective response requires reform of land administration, simplified planning standards, tenure security, infrastructure sequencing, and data-based urban management. The future of inclusive urbanization will depend less on headline megacities than on whether secondary cities can be governed before informality hardens into permanent spatial inequality.